Disaster Hazard Maps as Environmental Learning for Elementary School Students - Putri Mahanani; Puri Selfi Cholifah; Khusnul Khotimah; Ni Luh Sakinah Nuraini; Azni Yati Binti Kamaruddin; Indriyani Rachman; Murae Fumitoshi (Universitas Negeri Malang, 2025)
Abstract: All regions in the world are at risk of disaster. As part of the world, Indonesia is also an archipelagic country that is prone to disasters. One of the areas that is the focus of this research and development is the Malang area in East Java province. This area is one of the areas that recently experienced disasters in the form of volcanic eruptions, floods, and landslides in 2021-2023. The purpose of this study is to produce a geological and climatological natural disaster hazard map for learning in elementary schools. The research method used is the ADDIE research and development model which has 5 steps, namely Analysis, Design, Development, Implementation, and Evaluation. The research techniques and instruments that will be used are interviews, observation, and documentation. Data analysis in this study uses quantitative analysis with percentage techniques and qualitative analysis with a description of the product manufacturing and testing process. The results of the study showed that the geological and climatological natural disaster hazard map developed was declared valid by material experts and media experts with a percentage of 95% and 92%. After being tested in elementary schools, it received a 100% appeal rating from students. Student learning outcomes also show that 50% of students are included in the high category of learning outcomes improvement and 50% of students are in the medium category. These results indicate that the product can improve the quality of student learning. Abstrak: Seluruh wilayah di dunia mempunyai ancaman bencana. Sebagai bagian dari dunia, Indonesia juga merupakan negara kepulauan yang rawan terhadap bencana. Salah satu daerah yang menjadi fokus penelitian dan pengembangan ini adalah daerah Malang provinsi Jawa Timur. Daerah ini merupakan salah satu daerah yang baru-baru ini pada tahun 2021-2023 mengalami bencana berupa gunung meletus, banjir, dan tanah longsor. Tujuan penelitian ini adalah menghasilkan peta bahaya bencana alam geologi dan klimatologi untuk pembelajaran di sekolah dasar. Metode penelitian yang digunakan adalah model penelitian dan pengembangan ADDIE yang memiliki 5 langkah yaitu Analisis, Desain, Pengembangan, Implementasi dan Evaluasi. Teknik dan instrumen penelitian yang akan digunakan adalah wawancara, observasi dan dokumentasi. Analisis data dalam penelitian ini menggunakan analisis kuantitatif dengan teknik persentase dan juga kualitatif dengan deskripsi proses pembuatan dan pengujian produk. Hasil penelitian menunjukkan peta rawan bencana alam geologi dan klimatologi yang dikembangkan dinyatakan valid oleh ahli materi dan ahli media dengan persentase 95% dan 92%. Setelah diuji coba di SD mendapat penilaian daya tarik 100% dari siswa. Hasil belajar siswa juga menunjukkan bahwa 50% siswa termasuk pada peningkatan hasil belajar kategori tinggi dan 50% siswa pada kategori sedang. Hasil tersebut menunjukkan bahwa produk dapat meningkatkan kualitas pembelajaran siswa.